STUDY OF CLINICO-LABORATORY PROFILE IN ENTERIC FEVER AT TERTIARY CARE CENTRE IN RAJASTHAN - UPADHYAYA ALOK; MANDAVAT SAKSHI; JAIN PANKAJ; VISHNU AGARWAL (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective is to know the clinical profile of hospitalized patients with enteric fever and study the association of those clinical profiles with laboratory investigations. Methods: It was a hospital-based, prospective, cross-sectional, observational study, performed in the Department of Paediatric Medicine, SMS Medical College, Jaipur, over a period of 1 year from May 2021 to November 2022 to know the clinical profile of hospitalized patients of enteric fever and study association of that clinical profile with laboratory investigations. Prior permission from the institutional ethical committee was obtained. This study included a total of 100 children diagnosed with enteric fever. Results: Among study participants, the most common symptoms were fever (95), vomiting (39) and diarrhea (32). Other symptoms were pain abdomen (31), cough (23), anorexia (16), and headache (13). Among the signs, pallor was present in 26, icterus in 17, and hepato-splenomegaly in 16 children. Various hematological abnormalities found were as follows-leucopenia (87), leukocytosis (27), thrombocytopenia (16), pancytopenia (6), eosinopenia (66), and anemia (53). Hyponatremia and hypokalemia were found in 16 and 17 participants, respectively. Transaminitis was present in 32 participants. Mean Serum glutamic-oxaloacetic transaminase and serum glutamic-pyruvic transaminase was 48.6±65.2 and 48.9±71.8 IU/L, respectively. Positive C-reactive protein was found in 84 participants and blood culture was positive in 61 children. Among study participants various complications found were hepatitis, and bronchitis in 10 participants each followed by bronchopneumonia and encephalopathy in 2 participants each.